The Role of Incentives in Increasing Scientific Publications and Their Impact on Lecturer Career Development at Bina Darma University - Wati, Bungsu Widias; Helmi, Sulaiman (Yayasan Sinergi Kawula Muda, 2025)
Improving the academic productivity of lecturers is one of the main focuses of universities in addressing the challenges of globalization in education. Scientific publications play a strategic role in supporting lecturer career development while enhancing the institution's reputation. This study aims to analyze the effect of incentives on increasing scientific publications and their impact on the career development of lecturers at Bina Darma University. A quantitative approach was used with a survey involving 61 faculty members. Data were analyzed using SmartPLS 4. The results show that incentives do not significantly influence scientific publications or career development, while scientific publications positively affect career development. These findings suggest the need for administrative reform and enhanced research facilities to improve the effectiveness of incentive policies.